BRANDING RINTISAN DESA WISATA “JATISARI EDUPARK” DALAM MENINGKATKAN DAYA TARIK PENGUNJUNG - Riptanti, E.W.; Widyamurti, N.; Suherlan, Y.; Irianto, H.; Widiyanti, E.; Santoso, R.E. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
Jatisari Village is one of the development areas for porang cultivation in Wonogiri Regency. Porang (a kind of tuber) is one of Indonesia's export commodities. Knowing the potential and opportunities, the Jatisari Village Government has been developing a pilot tourist village in Tanduran, Jatisari Village's hamlet. The village government's land is used for cultivation expansion and as a porang education center . The Village Government does not have branding for tourist village destinations yet. The purpose of the activity is to build a pioneering brand for the Jatisari Village, which has certain characteristics for tourism. The implementation method is using Participatory Rural Appraisal (PRA), where the community is actively involved in branding design, starting with designing logos, visual identities, and applying them to tourist destination areas. This activity is synergized with the activity program of the village government. The results of the activity showed that the agreed-upon branding for the tourism village was "Jatisari Edupark." Jatisari Edupark presents learning activities for porang and rice cultivation, agritourism, outbound education, and culinary tours. The logo design consists of elements of saung, rice fields, mountains, and Porang plants that combine with harmonious colors. The logo design has been applied to the opening flier of "Jatisari Edupark" and the entrance tickets. This branding will increase the interest of tourists in visiting Jatisari Edupark. Keywords: agritourism, porang, PRA, logo, potency